Influence of Reverse Logistics on Performance of Food and Beverage Manufacturing Firms in Kenya - Mutuku, Alexander Kyalo; Moronge, Dr. Makori (International Journal of Supply Chain and Logistics, 2020)
Purpose: The purpose of the study was to assess the influence of reverse logistics on performance of food and beverage manufacturing firms in Kenya with an aim of making recommendations on proper use of reverse logistics management practices in manufacturing companies. Methodology: This research study adopted a descriptive research design approach. This study used probability sampling since the population and location of food and beverage manufacturing firms is known. Specifically, the study used stratified random sampling in order to account for the uneven distribution of firms in various towns. Based on distribution of firms in the 10 towns the study used proportions calculated in the population distribution to come up with a representative sample distribution. The proportions calculated give the number of firms to be included in the sample for each segment. Thereafter simple random sampling was used to select the names of food and beverage manufacturing firms in which data is to be collected. The study combined two methods in its data collection that is, questionnaires and key informant interviews. After data collection, quantitative data was coded using Statistical Package for Social Science (SPSS) version 20. Data was analysed through descriptive statistical methods such as means, standard deviation, frequencies and percentage. Inferential analyses were used in relation to correlation analysis and regression analysis to test the relationship between the four explanatory variables and the explained variable Results and conclusion: The response rate of the study was 92%. R square value of 0.647 means that 64.7% of the corresponding variation in performance of food and beverage manufacturing firms in Kenya can be explained or predicted by (product returns management, recycling management, disposal management and product repackaging) which indicated that the model fitted the study data. The results of regression analysis revealed that there was a significant positive relationship between dependent variable and independent variable at (Î² = 0.647, p=0.000 <0.05). The findings of the study concluded that product returns management, recycling management, disposal management and product repackaging have a positive relationship with performance of food and beverage manufacturing firms in Kenya. Unique contribution to theory, practice and policy: the study recommended that food and beverage manufacturing firms should embrace reverse logistics so as to improve performance and further researches should to be carried out in other sectors to find out if the same results can be obtained.